Effect of Internal Audit on Financial Management in Tertiary Educational Instutions: A Study of College of Education Oju, Benue State, Nigeria - Ikape Francis Ojiya; Omenka Sunday Oga (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2023)
Effective financial management is a key determinant to the success of any organization. Mismanagement of funds in educational institutions has become a stumbling block in the operations of educational institutions in Nigeria. Internal audit is of great importance in curbing financial mismanagement. This study investigated the effect of internal audit on financial management at the College of Education oju, Benue State. Four research objectives and hypotheses guided the study. Descriptive survey design was adopted, 71 principal staff were used as the population. Through census strategy the entire population was sampled and used for the study. Data were collected using questionnaires. Pearson product moment correlation statistics was used to test the hypotheses at 0.05 alpha level of significance. Major findings were that internal audit has significant effects on revenue generation, accountability in the use of funds, transparency in the use of funds and prevention of diversion of funds. Based on the findings, the researcher recommended among others that skilled auditors should be engaged to take up internal audit roles.